2013
DOI: 10.1063/1.4816285
|View full text |Cite
|
Sign up to set email alerts
|

In situ Raman monitoring of He2+ irradiation induced damage in a UO2 ceramic

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
5
30
1
Order By: Relevance
“…However, more bands were experimentally observed in Raman spectrum of UO 2 . Graves first observed a broad band around 576 cm −1 for Kr + implanted UO 2 samples, which was confirmed by other groups . It is a disorder/defect induced band and generally assigned to the normally forbidden first‐order longitudinal optical phonon (1LO), which can become Raman active through a loss of symmetry because of a breakdown in the selection rules.…”
Section: Introductionmentioning
confidence: 58%
“…However, more bands were experimentally observed in Raman spectrum of UO 2 . Graves first observed a broad band around 576 cm −1 for Kr + implanted UO 2 samples, which was confirmed by other groups . It is a disorder/defect induced band and generally assigned to the normally forbidden first‐order longitudinal optical phonon (1LO), which can become Raman active through a loss of symmetry because of a breakdown in the selection rules.…”
Section: Introductionmentioning
confidence: 58%
“…As a result of the interaction of the laser light with molecular vibrations, phonons or other excitations, the energy of the laser photons can be shifted up or down, which then contains information about the vibrational modes in the sample. Raman spectroscopy has been increasingly applied for the structural characterization of ion-beam modified materials, such as in carbides [36][37][38] and oxides [39][40][41][42]. More recently, micro-Raman spectroscopy has been used to characterize the damage created over the entire ion range [36,41,42] to provide new information on quantification of the damage and structure modification as a function of depth, and on enlightenment of possible synergistic effects due to both nuclear and electronic energy deposition to the materials [31].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Such conventional use of Raman spectroscopy does not allow probing depths exceeding several micrometers and especially does not provide quantitative analysis at a fixed damage level. Recent developments have shown that micro-Raman can be employed to quantify the damage in the wake of energetic ions from the surface of a crystal to the depth at which the ions come to rest (tens of micrometers) by analyzing thin cross sections of irradiated bulk samples [36,38,41,42]. Such cross-sectional approach provides several salient outcomes, such as distinctive effects of nuclear and electronic mechanisms resulting from the ion slowing down processes and information regarding the final structure of ion-irradiated materials along the ion path.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations